Menanamkan Semangat Entrepreneur Berbasis Pada Daur Ulang Limbah Plastik di SDN Panti 2 Jember - Ubaidillah, Mohammad; Shafany, Astry; Wardan, Nuril Maulidiyah; Nailah, Nurun; Maulina, Presilia Eka; Hoiriyah, Alfiatin; Azmi, Fatihah Ulul; Prasetyaningrum, Bintang Dwi; Puspito, Agung Nugroho (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This social project focuses on environmental conservation efforts through a waste recycling program aimed at SDN Panti 2 students. The main objective of this project is to increase students' awareness and understanding of the importance of keeping the environment clean and teach them practical ways to recycle waste. This program consists of a series of educational activities that begin with counseling about the types of waste, the negative impact of waste on the environment, as well as recycling techniques and benefits. After that, students are invited to participate in various creative activities using used goods. The methodology used in this project is with conventional methods, namely presentations, discussions, games, and practicums. The results of this project show a significant increase in students' knowledge and awareness of the importance of waste recycling. The success of this program cannot be separated from the full support of the school and also the contribution of SDN Panti 2 students. And this project is a form of introducing the concept of entrepreneurship to students from the results of used goods. The main purpose of this project is to increase the value of students' creativity in making useful goods from recycled materials and introduce the economic potential of recycled products. It is hoped that students can develop positive habits that have a long-term impact on environmental preservation and entrepreneurial skills.